Research through Collaborative Relationships: A Middle Ground for Reciprocal Transformations and Translations? - Briones, Claudia Noemi (2017)
Joanne Rappaport’s article has two main virtues. On the one hand, she provides a thoughtful summary of very diverse experiences of collaborative research. On the other, she expands the fi eld of vision of our discussions by means of key displacements of focus: from collaborative research to research through collaborative relationships; and from products to processes. She does so by means of a very ethnographic contextualization and historization of the initiatives of La Rosca de Investigación y Acción Social (Circle of Social Research and Action), a group deeply related to Orlando Fals Borda’s appealing methodology of “action research.